Mortalités estivales de l'huître Crassostrea gigas dans le bassin d'Arcachon : facteurs du milieu, aspects biochimiques et histologiques - Maurer, Daniele; Comps, Michel (European Aquaculture Society, 1986)
Previous pathological studies have not permitted to implicate infectious disease in summer mortalities of oysters Crassostrea gigas, in the Arcachon bay. In 1983, these summer mortalities, occurring mostly among 1 year old oysters, have been the subject of new investigations. In order to establish the causes of mortalities, oysters of the same origin were held in two areas characterized by different prevalence of mortality for 6 months, during which measurements of physiological and biochemical condition and certain histological observations were made. The study has been completed by environmental observations. Different rates of mortality appeared between the two selected areas: 30 %in Taussat in the upper part of the bay, under a continental influence and 3 % in Cap Ferret, under an oceanic influence. Among environmental factors, temperature showed the most significant difference between the two sites, with the highest values of 27°C in Taussat and 22°C in Cap Ferret. In the two areas, the nutrient levels appeared to be similar and no deoxygenation was ever observed during the summer. Statistical size difference between surviving and dead oysters was not observed, and the sex ratio data indicated that the mortality was not selective against females or males. Mortality occurred after gradual decrease of the relative dry weight and the condition index of the oysters, and was more marked in Taussat. In both groups studied, the timing of mortality also coincided with the decline in carbohydrate content from 9 % of the dry weight to values as low as 0,7 %. The histological studies confirmed the absence of pathogens, and showed a change in the digestive cell structure: a thinning of the digestive tubule epithelium resulting from a loss of the apical cytoplasm in response to exposure at elevated temperature. This epithelial thinning appeared to be related to the formation of autolysosomes in the digestive cells. This change was greater in Taussat oysters than in those of Cap Ferret. These data suggest that hi.gh ...